Diseño del plan de mantenimiento programado de la primera etapa del sistema de producción críogénica de una planta de separación de gases del aire - Lino, Acosta (2010)
The main objective set out in this thesis has to do with the need to improve maintenance activities within the industry in the area of maintenance, with the aim of turning them into an argument with a priority boost competitiveness of it. In addition it also carries a description of software maintenance is the same as one example of many that exist today and that can be tailored to the needs of the company. The ability to maintain business relationships with customers worldwide, makes it require efficient firms that are ready for change, so adapt technological innovations in the industries of our environment is a necessity becomes urgent.